2022
DOI: 10.3390/su14095264
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation of Chinese Provincial Industrial System Based on Network DEA Method

Abstract: The operation process of the Chinese provincial industrial system consists of four stages, namely the production (P) stage, wastewater treatment (WWT) stage, solid waste treatment (SWT) stage, and sulfur dioxide treatment (SDT) stage. Based on this structure, a four-stage data envelopment analysis (DEA) model is developed to evaluate the eco-efficiency, production efficiency, wastewater treatment efficiency, solid waste treatment efficiency, and sulfur dioxide treatment efficiency of provincial industrial syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Existing research constitutes an important basis for this study, but the following deficiencies still exist. First, most of the current studies on IE are focused on the provincial level [47], urban clusters [10,48], or industrial parks, and relatively few studies from watershed perspective. Second, the existing research on IE mainly adopts a single method and perspective and pays insufficient attention to the internal mechanism when analyzing the influence factors of IE, which cannot fully reflect the connotation of IE.…”
Section: Research Gapmentioning
confidence: 99%
“…Existing research constitutes an important basis for this study, but the following deficiencies still exist. First, most of the current studies on IE are focused on the provincial level [47], urban clusters [10,48], or industrial parks, and relatively few studies from watershed perspective. Second, the existing research on IE mainly adopts a single method and perspective and pays insufficient attention to the internal mechanism when analyzing the influence factors of IE, which cannot fully reflect the connotation of IE.…”
Section: Research Gapmentioning
confidence: 99%
“…China is currently undergoing a pivotal economic transformation as its rapid industrialization has led to high economic growth (He et al, 2022). This industrial boom, however, has propelled the nation to the position of the world's largest energy consumer and carbon dioxide emitter, with its downsides being evident in escalating pollution, increased energy consumption, and carbon emissions (Hu and Zheng, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple input and output indicators can be selected when calculating the target efficiency values as input and output elements of rural tourism, respectively. The literature [28][29][30][31] selected the DEA method to analyze the economic effects of the tourism industry in the Guarquecaba region of Brazil and the strength of the effects. The results of the study found that relying on the dual forces of foreign investment and imports to develop the country's economy, the strength of the contribution of both was found to dominate the local tourism industry and the subsequent proof of this argument, due to the successive withdrawal of foreign investment, which led to a heavy blow to the Brazilian tourism industry, which has since fallen into disarray.…”
Section: Introductionmentioning
confidence: 99%